Peningkatan Asam Lemak Tak Jenuh (Pufas) Dengan Menggunakan Rhizopus Oryzae Dalam Fermentasi Bekatul - Eli Sahara; F. Yosi; Sofia Sandi (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2016)
Sahar et al, 2016.Â Increasing of Polyunsaturated Fatty Acids (Pufas) by Using Rhizopus Orizae in theÂ  Fermented Bran. JLSO 5(1):79-85.This study aimed to determine 1) the volume of inoculums and the optimum incubation time during the fermentation process; 2) the types of polyunsaturated fatty acids during fermentation; and 3) the presence of omega-3 essential fatty acids in bran fermentation. The study used fermentation method using R. oryzae. Chromatography-Mass Spectroscopy (GC-MS) was used to determine the type of polyunsaturated fatty acids and omega-3 contained in the fermented bran. This study used 9 treatments, V3H3, V3H6, V3H9, V5H3, V5H6, V5H9, V7H3, V7H6, and V7H9. The results showed 1) the volume of inoculums and the fermentation time V7H3 was the most optimum result; 2) there were 13 types of polyunsaturated fatty acids, and 3) there was the content of omega-3 in bran fermented.